155 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view of 155 Charles Street, located at the southeast corner of Charles Street and Silver Place. Signage adorns the facade of the building, which faces north towards Silver Place, and commercial products are displayed in the building's storefront windows. Street lamps, traffic signals and a sign for a train stop are visible in the photograph, as is a set of stairs leading to a pedestrian bridge that stretches across Charles Street. A parked automobile and pedestrians can be seen in front of the building. The west elevations of two apartment buildings located on West Cedar Street are visible in the background of the photograph. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs